RISET EKSPERIMENTAL PENGAUDITAN: EVOLUSI DAN TOPIK KONTEMPORER - Utami, Intiyas; Nahartyo, Ertambang (Jurnal Akuntansi dan Keuangan Indonesia, 2013)
Behavioral research in accounting is paying more attention to auditing issue since auditing relies heavily on judgment and decision making process. This article describes the development of experimental auditing research and identifies the potentials for contemporary research by documenting the international article from the 1970s to 2000s. This article is organized into the following sections. After the introductory part, it discusses the nature of experimental auditing research (EAP), the evolution of international EAP, topics of contemporary EAP, and the development of EAP in Indonesia. Based on the analysis of international EAP articles, we suggest that future research focuses on risk-based auditing, modes of presentation of audit information, fraud risk assessment, analytical procedure, interaction between auditors and clients (negotiation and agreement) and interaction between auditors with their auditor counterparts (brainstorming).